Analisis Regresi Faktor-faktor yang Mempengaruhi Prestasi Belajar Siswa kelas XI di MAPK Al-Hidayah Baron Nganjuk - Wardani, Dian Kusuma; Khikmah, Niswatul (Lembaga Penelitian Pengabdian Masyarakat Universitas KH. A. Wahab Hasbullah, 2021)
Factors are things, circumstances, or events that play a role and influence things that will happen. The level of student achievement depends on the factors that influence it. There are two factors that can influence, including factors contained within students (internal factors) and factors that exist from outside students (external factors). This study aims to determine the factors that influence the learning achievement of class XI MAPK Al-Hidayah Baron Nganjuk students. This research is quantitative, the research design uses multiple regression analysis. Collecting data through documentation, questionnaires or questionnaires and report cards. The result of this research is a regression analysis model formed by predictor variables that have a significant influence on student learning outcomes, namely physical variables, interest variables, motivation variables and family environment variables. Variables that do not have a significant effect on the model are the IQ variable, the school environment variable and the community environment variable. The conclusion of the study is that the factors that affect the learning outcomes of class XI students at XI MAPK Al-Hidayah Baron Nganjuk are IQ factors, physical factors, motivational factors, family environmental factors, school environmental factors.